THE ECO-THEOLOGY OF ḤIMĀ AND ḤARĪM: RECONSTRUCTING THE AUTHORITY OF GREEN SPACE CONSERVATION IN PROPHETIC TRADITIONS: Ekoteologi Ḥimā dan Ḥarīm: Rekonstruksi Otoritas Konservasi Ruang Hijau dalam Tradisi Kenabian - Siti Kholidah; Novita Sari, Ira; Sekti Prayet, Nanda; Saputra, Edriagus (International Journal of Research, 2025)
Abstract The escalating ecological crisis, marked by deforestation, the reduction of green spaces, contamination of water resources, and global climate change, reflects the inadequacy of conservation approaches that have largely relied on formal regulations without sufficient support from the moral and spiritual consciousness of society. On the other hand, Islamic environmental discourse remains predominantly confined to the level of individual ethics and has not extensively addressed ecological spatial governance as a structural instrument of conservation. This study aims to analyze the concepts of ḥimā and ḥarīm in the Prophet’s hadith as normative foundations for green space conservation, reconstruct ecological authority within the Prophetic tradition, and explain their relevance in the context of contemporary environmental management. This research employs a qualitative library-based method (library research) with a thematic hadith (mawḍū‘ī) approach. Primary data were obtained from the major hadith collections and classical fiqh literature, while secondary data were drawn from scholarly articles and studies on Islamic ecotheology. The analysis includes the interpretation of hadith meanings (ma‘ānī al-ḥadīth) and ecological contextualization. The findings reveal that the concept of ḥimā functions as a conservation mechanism based on public authority to protect the sustainability of natural resources, while ḥarīm serves as a protective zone for vital resources, particularly water, from activities that may disrupt ecological balance. These findings affirm that the Prophet’s hadith not only embodies environmental ethics but also provides a systematic, preventive, and relevant model of conservation governance for strengthening environmental policies based on Islamic values in the modern era. Keywords: Ḥimā, Ḥarīm, Conservation, Hadith Ecotheology